ATTITUDE ANALYSIS OF “THE GUARDIAN” EDITORIAL: LOCKDOWN POLICY AND THE GOVERNMENT - Ratih Laily Nurjanah (JOALL (Journal of Applied Linguistics and Literature), 2021)
This study aims to analyze the presented attitude based on the choice of words in an editorial published by The Guardian on November 5th, 2020 entitled “The Guardian View on the New Lockdown: Fewer Promises, Better Performance Needed”.  One of the most relevant discourses to be analyzed is editorial section of newspaper that is considered as the purest part of mass media reflected ideology, or in this case, political stance. This is a qualitative study using the method of Systemic Functional Language framework with the specification of interpersonal meaning especially appraisal analysis with 22 appraising items taken from the editorial as the sources of data. The findings show that The Guardian is more likely not standing on the same side as the government by giving more negative attitude than the positive ones in terms of affects, judgment, and appreciation. Getting involved in attitude analysis as a part of SFL is considered important in ELT process to help students use language appropriately started from small unit like word.